EFFECTS OF COGNITIVE ORIENTATION PROGRAM ON THE PSYCHOLOGICAL PROCESSES OF WRITING IN STUDENTS OF THE CONSTITUTIONAL PROVINCE OF CALLAO - Velarde Consoli, Esther (2014)
This research had as objective develop, implement and validate lexicons (write to the dictation of words and sentences to assess mastery of the phonological path and write words to assess the visual route spelling), a program of stimulation of the psychological processes of the writing: syntactic process (ordering and complete words, placing punctuation) and planning of measured Scripture through the construction of a sequence of stories and the drafting of a descriptive and narrative text. The sample was comprised of 111 students in 2nd and 3rd grade primary school (56 of the control group and 55 of the experimental group) of two state educational institutions of Callao. It was observed an increase in all the tasks mentioned except in the drafting of texts and narratives due to time factors. From the result we recommend the dissemination of this programme with the aim of forming students with high levels of mastery especially in productive writing.